Neurotoxicologically Outcomes of Perinatal Chlordiazepoxide Exposure on the Fetal Prefrontal Cortex Cells in Rat Pup - Parsa, Yekta; Nadia Sharifi, Zahra; Ghaffarpasand, Fariborz; Parsa, Tina; Zarrindast, Mohammad-Reza; Jangholi, Ehsan; Yadollah-Damavandi, Soheila; Aghazadeh, Mohammad Hossein; Shahi, Farshad; Movassaghi, Shabnam (Galen Medical Journal, 2025)
Background: Chlordiazepoxide is a benzodiazepine which is widely used as an anxiolytic, sedative and muscle-relaxant and its effects on neurodevelopment is yet to be identified. The aim of the current experimental study was to determine the effects of prenatal exposure to chlordiazepoxide on development of the prefrontal cortex (PFC). Materials and Methods: A total number of 9 pregnant Wister rats that were randomly assigned to three groups receiving standard rat food and drinking water ad libitum (n=3) or chlordiazepoxide (10 mg/kg) (n=3) and an equal volume of vehicle (0.9% NaCl) (n=3) intraperitoneal (i.p.) injection once daily from first to 21st day of gestation, respectively. At the end of the experiment, 14-day-old neonatal rat pups (n=8 per each group) were sacrificed and their PFC cells were extracted. Mitochondria were extracted from the PFC cells and their level of reactive oxygen species (ROS), protein density, Glutathione (GSH) content, mitochondrial membrane potential (MMP), swelling, cytochrome c release and ATP level was identified. We also performed the Nissl staining, DNA fragmentation assay and RNA extraction and real-time polymerase chain reaction (PCR) on PFC cells. Results: We found that isolated mitochondria from rat pups receiving chlordiazepoxide (E), had significantly higher ROS formation (P<0.001), decreased GSH (P<0.001), lower MMP (P<0.001), higher mitochondrial swelling (P<0.001), decreased ATP level (P<0.001), increased cytochrome c release (P<0.001) and higher Bax (P<0.001), p53 (P<0.001), cytochrome c (P<0.001) and caspase 8 mRNAs (P<0.001). The Nissle-stained neurons decreased while the apoptosis significantly increased (P<0.001). Conclusions: The results of this in vivo study provide evidence regarding negative effects of prenatal exposure to chlordiazepoxide on PFC.